“Nalar Fenomenologi”; Mahkamah Konstitusi dalam Pusaran Kekuasaan dan Bahaya Krisis Weltanschauung - Susanto Polamolo (Jurnal Konstitusi, 2016)
Constitutional Court who was born as one of the reforms agenda in the continued process of judicial power itself into an independent institution that is at the forefront in  guarding  the  constitution.  As  an  agency  that  handles  matters constitutional, posisiny is clearly confronted with the vortex power of the oligarchs who seemed never be separated from the Indonesian constitutional journey. Struggle not only with critics but also systemic critique of scientific laws, which the agency is expected to not thick with legalistic positivism absolutizing the workings of the law and the constitution. Besides, what is the most feared and to be consequences if the judges are in crisis Weltanschauung. This is where the need to check the perspective that not only cast a normative critique, but also reflective criticism, as an affirmation of the political and dismantle structural hegemony explore perspectives on the human being as the central value of justice.